Not All Price Endings Are Created Equal: Price Points and Asymmetric Price Rigidity - Avichai Snir; Daniel Levy; Alex Gotler; Haipeng (Allan) Chen (Emory University, 2014)
Using data from three sources (a laboratory experiment, a field study, and a large US supermarket chain), we document a surprising asymmetric behavior of 9-ending prices: they are more rigid upward, but not downward, in comparison to non 9-ending prices. The data from the lab experiment and the field study suggest that shoppers are less likely to notice higher prices when they end with 9, or price increases when the new prices end with 9, in comparison to other endings. The consumers' misperception seems to be caused by their use of 9-endings as a signal for low prices, which interferes with price information processing. The supermarket data suggest that retail price setters respond strategically to the consumer misperception by setting 9-ending prices more often after price increases than after price decreases. 9-ending prices, therefore, usually increase only if the new prices are also 9-ending. Consequently, 9-ending prices exhibit asymmetric rigidity: they are more rigid than non 9-ending prices upward but not downward.
Keywords: E31; L16; C91; C93; D03; D80; M31; 330; Price Points; Price Recall; Sticky Prices; Rigid Prices; Price Rigidity; Price Adjustment; 9-Ending Prices; Psychological Prices; Asymmetric Price Adjustment; Price stickiness; Adjustment